Evaluation of dipeptide nitriles as inhibitors of rhodesain, a major cysteine protease of Trypanosoma brucei - Schirmeister, Tanja; Schmenger, Torsten; Krauth-Siegel, Renate (Bioorganic & medicinal chemistry letters, 2017)
A series of dipeptide nitriles known as inhibitors of mammalian cathepsins were evaluated for inhibition of rhodesain, the cathepsin L-like protease of Trypanosoma brucei. Compound 35 consisting of a Leu residue fitting into the S2 pocket and a triarylic moiety consisting of thiophene, a 1,2,4-oxadiazole and a phenyl ring fitting into the S3 pocket, and compound 33 with a 3-bromo-Phe residue (S2) and a biphenyl fragment (S3) were found to inhibit rhodesain in the single-digit nanomolar range. The observed steep structure-activity relationship could be explained by covalent docking simulations. With their high selectivity indices (ca. 200) and the good antitrypanosomal activity (8μM) the compounds represent promising starting points for new rhodesain inhibitors.